Hypergeometric Function - 15.7 Continued Fractions

From testwiki
Revision as of 11:39, 28 June 2021 by Admin (talk | contribs) (Admin moved page Main Page to Verifying DLMF with Maple and Mathematica)
(diff) ← Older revision | Latest revision (diff) | Newer revision β†’ (diff)
Jump to navigation Jump to search


DLMF Formula Constraints Maple Mathematica Symbolic
Maple
Symbolic
Mathematica
Numeric
Maple
Numeric
Mathematica
15.7#Ex1 t n = c + n subscript 𝑑 𝑛 𝑐 𝑛 {\displaystyle{\displaystyle t_{n}=c+n}}
t_{n} = c+n

t[n] = c + n
Subscript[t, n] == c + n
Skipped - no semantic math Skipped - no semantic math - -
15.7#Ex2 u 2 ⁒ n + 1 = ( a + n ) ⁒ ( c - b + n ) subscript 𝑒 2 𝑛 1 π‘Ž 𝑛 𝑐 𝑏 𝑛 {\displaystyle{\displaystyle u_{2n+1}=(a+n)(c-b+n)}}
u_{2n+1} = (a+n)(c-b+n)

u[2*n + 1] = (a + n)*(c - b + n)
Subscript[u, 2*n + 1] == (a + n)*(c - b + n)
Skipped - no semantic math Skipped - no semantic math - -
15.7#Ex3 u 2 ⁒ n = ( b + n ) ⁒ ( c - a + n ) subscript 𝑒 2 𝑛 𝑏 𝑛 𝑐 π‘Ž 𝑛 {\displaystyle{\displaystyle u_{2n}=(b+n)(c-a+n)}}
u_{2n} = (b+n)(c-a+n)

u[2*n] = (b + n)*(c - a + n)
Subscript[u, 2*n] == (b + n)*(c - a + n)
Skipped - no semantic math Skipped - no semantic math - -
15.7#Ex4 v n = c + n + ( b - a + n + 1 ) ⁒ z subscript 𝑣 𝑛 𝑐 𝑛 𝑏 π‘Ž 𝑛 1 𝑧 {\displaystyle{\displaystyle v_{n}=c+n+(b-a+n+1)z}}
v_{n} = c+n+(b-a+n+1)z

v[n] = c + n +(b - a + n + 1)*z
Subscript[v, n] == c + n +(b - a + n + 1)*z
Skipped - no semantic math Skipped - no semantic math - -
15.7#Ex5 w n = ( b + n ) ⁒ ( c - a + n ) ⁒ z subscript 𝑀 𝑛 𝑏 𝑛 𝑐 π‘Ž 𝑛 𝑧 {\displaystyle{\displaystyle w_{n}=(b+n)(c-a+n)z}}
w_{n} = (b+n)(c-a+n)z

w[n] = (b + n)*(c - a + n)*z
Subscript[w, n] == (b + n)*(c - a + n)*z
Skipped - no semantic math Skipped - no semantic math - -
15.7#Ex6 x n = c + n - ( a + b + 2 ⁒ n + 1 ) ⁒ z subscript π‘₯ 𝑛 𝑐 𝑛 π‘Ž 𝑏 2 𝑛 1 𝑧 {\displaystyle{\displaystyle x_{n}=c+n-(a+b+2n+1)z}}
x_{n} = c+n-(a+b+2n+1)z

x[n] = c + n -(a + b + 2*n + 1)*(x + y*I)
Subscript[x, n] == c + n -(a + b + 2*n + 1)*(x + y*I)
Skipped - no semantic math Skipped - no semantic math - -
15.7#Ex7 y n = ( a + n ) ⁒ ( b + n ) ⁒ z ⁒ ( 1 - z ) subscript 𝑦 𝑛 π‘Ž 𝑛 𝑏 𝑛 𝑧 1 𝑧 {\displaystyle{\displaystyle y_{n}=(a+n)(b+n)z(1-z)}}
y_{n} = (a+n)(b+n)z(1-z)

y[n] = (a + n)*(b + n)*(x + y*I)*(1 -(x + y*I))
Subscript[y, n] == (a + n)*(b + n)*(x + y*I)*(1 -(x + y*I))
Skipped - no semantic math Skipped - no semantic math - -